2018
DOI: 10.1371/journal.pone.0191321
|View full text |Cite|
|
Sign up to set email alerts
|

Genotype-by-environment interactions affecting heterosis in maize

Abstract: The environment can influence heterosis, the phenomena in which the offspring of two inbred parents exhibits phenotypic performance beyond the inbred parents for specific traits. In this study we measured 25 traits in a set of 47 maize hybrids and their inbred parents grown in 16 different environments with varying levels of average productivity. By quantifying 25 vegetative and reproductive traits across the life cycle we were able to analyze interactions between the environment and multiple distinct instance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 41 publications
5
35
0
Order By: Relevance
“…Furthermore, the enrichment of non-syntenic genes in non-PAV SPE and PAV SPE gene sets, along with the enrichment for expression complementation in the hybrids across genotypes and tissues for these genes, could contribute to the superior adaptation of hybrid plants to environmental stresses. The high genotype-and tissuespecific nature of non-PAV SPE and PAV SPE genes could also contribute to the diversified manifestation of heterosis across traits, environments, and genetic combinations (Flint-Garcia et al, 2009;Schnable and Springer, 2013;Marcon et al, 2017;Li et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the enrichment of non-syntenic genes in non-PAV SPE and PAV SPE gene sets, along with the enrichment for expression complementation in the hybrids across genotypes and tissues for these genes, could contribute to the superior adaptation of hybrid plants to environmental stresses. The high genotype-and tissuespecific nature of non-PAV SPE and PAV SPE genes could also contribute to the diversified manifestation of heterosis across traits, environments, and genetic combinations (Flint-Garcia et al, 2009;Schnable and Springer, 2013;Marcon et al, 2017;Li et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Modern maize production has benefited from heterosis, a widely observed phenomenon in which hybrids show superior performances relative to their inbred parents (Flint-Garcia et al, 2009;Birchler et al, 2010). However, the manifestation of heterosis has been shown to vary greatly across traits and environments for a given hybrid (Flint-Garcia et al, 2009;Li et al, 2018), making it unlikely to be explained by a single mechanism. Indeed, the molecular underpinnings for heterosis are still under debate (Schnable and Springer, 2013;Wallace et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A favourable environment will result in higher outputs, whereas under stress conditions a greater amount of energy is utilized to adapt to the adverse conditions. In maize, it has also been observed that environment influences the degree of heterosis for yield traits (Li et al, 2018). The latter authors concluded that environment is critical and affects the degree of heterosis for a trait within a genotype.…”
Section: Regression Analysis Between Genetic Distance and Heterosismentioning
confidence: 99%
“…This difference might be due to the concept of "buffering," which posits that a heterozygous population shows higher stability than a homozygous population. A hybrid's response to environmental stimuli will result in an altered degree of heterosis across different environments (Allard & Bradshaw, 1964;Li et al, 2018). In addition, seed cotton yield is a multiplicative trait to which many other individual traits contribute; therefore, it is unlikely that all traits of a genotype will perform identically in different environments.…”
Section: Regression Analysis Between Genetic Distance and Heterosismentioning
confidence: 99%
“…Although G×E has been well-documented and studied in plant and animal species, it remains a significant challenge to breeding programs (Crossa 2012; de Leon et al 2016; Xu 2016; Li et al 2018). Obtaining a rigorous assessment of G×E effects requires phenotypic evaluation in a wide range of environments and breeder choices about the level of trait instability across environments that will be tolerated.…”
Section: Introductionmentioning
confidence: 99%